2021
DOI: 10.1002/pmrj.12565
|View full text |Cite
|
Sign up to set email alerts
|

Investigating inpatient rehabilitation outcomes of patients with intensive care unit–acquired weakness, and identifying comorbidities associated with unfavorable outcomes

Abstract: Introduction Data are consistent on the benefits of inpatient rehabilitation for intensive care unit–acquired weaknesses (ICUAW), including critical illness myopathy, critical illness polyneuropathy, critical illness polyneuromyopathy, and disuse atrophy. This study focuses on the effects of inpatient rehabilitation on patients with ICUAW, specifically those with a clinical pattern of proximal muscle weakness and sensory sparing. Objectives To evaluate the impact of inpatient rehabilitation on patients with IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…some studies suggested that ICU-AW may occur within several hours after patients receiving mechanical ventilation, the early intervention can reduce incidence of ICU-AW, and the earlier intervention can achieve the better effect. [10–12] So it has an important clinical value to explore an optimum proposal for early progressive mobilization. [13]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…some studies suggested that ICU-AW may occur within several hours after patients receiving mechanical ventilation, the early intervention can reduce incidence of ICU-AW, and the earlier intervention can achieve the better effect. [10–12] So it has an important clinical value to explore an optimum proposal for early progressive mobilization. [13]…”
Section: Discussionmentioning
confidence: 99%
“…some studies suggested that ICU-AW may occur within several hours after patients receiving mechanical ventilation, the early intervention can reduce incidence of ICU-AW, and the earlier intervention can achieve the better effect. [10][11][12] So it has an important clinical value to explore an optimum proposal for early progressive mobilization. [13] In this study, The MRC score and Barthel index score of the intervention group were significantly higher than those of the control group, suggesting that early progressive mobilization can effectively improve the muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
“…This study excluded patients under RIC-1-8, 10-13, 17-19, or 21 who are CMS's “60 Percent Rule” complaint. However, 55 patients with intensive care unit–acquired weakness 32 equivalent to critical illness myopathy who are considered CMS compliant under RIC-6 were included in this study because they are often coded as having debility (IGC16) under RIC-20.…”
Section: Methodsmentioning
confidence: 99%
“…The reported incidence of ICU-AW is variable, partially due to inconsistent diagnostic criteria, ranging from 7% to 76% of ICU patients, with an approximate estimate of 40% in the general ICU population ( Appleton et al, 2015 ). Baseline risk factors that increase the likelihood of developing ICU-AW are age ( Moisey et al, 2013 ), and medical comorbidities such as chronic heart failure, anemia, and renal disease ( Rudra et al, 2021 ); risk factors that develop within the ICU are duration of mechanical ventilation, diagnosis of sepsis, severity of critical illness, hyperglycemia, use of glucocorticoids and neuromuscular blockade, and prolonged immobilization ( Yang et al, 2018 ). There are currently no targeted therapies that can prevent or reverse the natural trajectory of ICU-AW, signifying an urgent and unmet need in the treatment of this condition.…”
Section: Introductionmentioning
confidence: 99%